The Additional Cost of Operating Rural Schools: Evidence From Vermont. (February 2021) - Kolbe, Tammy; Baker, Bruce D.; Atchison, Drew; Levin, Jesse; Harris, Phoebe
State policymakers wrestle with long-standing questions and concerns about how to best provide additional fiscal support to rural school districts to ensure their students have access to adequate educational opportunities. In this study, we describe how one state developed empirically based estimates for the additional cost of operating rural schools, typified by small enrollment and location in sparsely populated areas. The study's findings clarify that school size and location are relevant, but distinct, cost factors that should be accounted for state school finance policies. Additionally, the study provides a model for how other states might leverage administrative data and apply education cost modeling to estimate cost differences for rural schools that can be used to inform state school finance policy.